2014
DOI: 10.1007/s12311-014-0619-7
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Damage in Machado-Joseph Disease

Abstract: Machado-Joseph disease (SCA3) is the most frequent spinocerebellar ataxia worldwide and characterized by remarkable phenotypic heterogeneity. MRI-based studies in SCA3 focused in the cerebellum and connections, but little is known about cord damage in the disease and its clinical relevance. To evaluate the spinal cord damage in SCA3 through quantitative analysis of MRI scans. A group of 48 patients with SCA3 and 48 age and gender-matched healthy controls underwent MRI on a 3T scanner. We used T1-weighted 3D im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 21 publications
3
31
1
Order By: Relevance
“…Both cerebellar and brain stem structures presented significant correlation with SARA, 29,32,33 ICARS, 16,33 disease duration, 32,33 and CAG repeat expansions length (On-line Table 1 and Fig 2). A single study evaluated semiautomated cervical spine volumetric analysis and found significant atrophy in SCA3/MJD, which correlated with longer disease duration.…”
Section: 31-34mentioning
confidence: 84%
See 4 more Smart Citations
“…Both cerebellar and brain stem structures presented significant correlation with SARA, 29,32,33 ICARS, 16,33 disease duration, 32,33 and CAG repeat expansions length (On-line Table 1 and Fig 2). A single study evaluated semiautomated cervical spine volumetric analysis and found significant atrophy in SCA3/MJD, which correlated with longer disease duration.…”
Section: 31-34mentioning
confidence: 84%
“…Regarding volumetric studies, cerebellar hemispheres and vermis, whole brain stem, midbrain, pons, medulla oblongata, cervical spine, caudate and putamen nuclei, and thalamus seem to be the best target regions as surrogate outcomes in SCA3/MJD according to cross-sectional studies. 16,29,24,32,33 In the study by Schulz et al, 29 the stepwise inclusion of the pons and medulla oblongata together explained 53% of the variance in SARA in a linear regression model, and in another study, the cross-sectional area of the cervical spine explained 49.1% of SARA scores in a regression model built with disease duration and cerebellar volume. 9 Some minor differences in the results across studies might be related to technical differences between semiautomated and automated analyses and differences between VBM and surface analysis (FreeSurfer).…”
Section: Mr Volumetric Analysis Sca1mentioning
confidence: 94%
See 3 more Smart Citations